Umkämpfte Zivilgesellschaft : Mit menschenrechtsorientierter Gemeinwesenarbeit gegen Ideologien der Ungleichwertigkeit - Bringt, Friedemann (2021)
A trend can be observed whereby violently racist attitudes are shared by both extreme right-wing and reactionary bourgeois milieus and are becoming normalized in public discourse. This situation reflects what sociological research has attested for years: Civil societies are not necessarily progressive, democratic, and public welfare oriented. They can be reactionary, anti-democratic, and aggressively self-interested. With a view to this ""dark side of civil society,"" the study examines projects of human rights-oriented community work (GWA) designed specifically for such problem constellations. The study examines the conditions for success of socio-spatial processes of change towards a more democratic everyday culture through GWA and develops proposals for their conceptual further development.